Solid state NMR study of 1, 3imidazolidine-2-thione, 1, 3-imidazolidine-2-selenone and some of their N-substituted derivatives. Issue 1 (2004) - Wazeer Wazeer, Mohamed I. M. Mohamed I. M.; Isab Isab, Anvarhusein A. Anvarhusein A.; El‒Rayyes El‒Rayyes, Ali Ali
Abstract : Solid‒state NMR spectra were recorded for 1, 3-imidazolidine-2-thione, 1, 3-imidazolidine-2-selenone and some of their N-substituted derivatives. Spinning side-bands of thione and selenone carbons were analysed to yield chemical shift anisotropies for these carbons. The NMR spectrum of imidazolidine-2-thione (Imt) showed some evidence for the presence of thiol tautomer. Molecular computations were carried out for Imt and its N-methyl derivative to yield relative energies of various tautomers.